2014
DOI: 10.1002/stem.1803
|View full text |Cite
|
Sign up to set email alerts
|

Twist-1, A Novel Regulator of Hematopoietic Stem Cell Self-Renewal and Myeloid Lineage Development

Abstract: Transcription factor Twist-1 plays essential roles in specification and differentiation of mesoderm-derived tissues. Growing evidences now link Twist-1 to the acquisition of stem-celllike properties. However, the role of Twist-1 in hematopoietic stem cell (HSC) remains largely uncharacterized. We report that Twist-1 is more highly expressed in murine HSC and its expression declines with differentiation. To investigate Twist-1 gene function, retroviral-mediated overexpression or removal experiments are performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…33 In agreement, we found that Twist1 loss suppressed Gata1 expression in AGM-derived HSPCs, impairing myeloid differentiation ( Figure 2E,G). However, we observed no change in expression of the myeloid transcription factor Spi1 (Pu.1) in Twist1 2/2 embryos.…”
Section: Discussionsupporting
confidence: 84%
“…33 In agreement, we found that Twist1 loss suppressed Gata1 expression in AGM-derived HSPCs, impairing myeloid differentiation ( Figure 2E,G). However, we observed no change in expression of the myeloid transcription factor Spi1 (Pu.1) in Twist1 2/2 embryos.…”
Section: Discussionsupporting
confidence: 84%
“…Studies show that increased expression of Twist-1 increases the expression of PU.1 and GATA-1 and reduces GATA-3. Therefore, it seems that Twist-1 causes differentiation induction of HSCs to myeloid lineage through the induction of myeloid specification genes and decreased expression of lymphoid specification genes [42].…”
Section: Physiological Roles Of Twist In Bm Nichementioning
confidence: 99%
“…Both c-Mpl and Tie2 are markers of LT-HSCs and play an important role in the regulation of LT-HSC quiescence [45,46]. Dong et al was shown that Twist-1 overexpression causes changes in gene expression of Runx1, c-Mpl and Tie2 transcription factors [42]. Thus, given the importance of Twist-1 expression in LT-HSCs and its relationship with c-Mpl and Tie2 expression, it may play an important role in survival, differentiation and selfrenewal of LT-HSC, which requires further studies to be proved.…”
Section: Physiological Roles Of Twist In Bm Nichementioning
confidence: 99%
See 1 more Smart Citation
“…59 TWIST1 is highly expressed in hematopoietic stem cells and promotes their self-renewal and stemness. 60 It also contributes to epithelial-mesenchymal transition 61 and tumor cell tissue invasion and metastasis formation in gastric, 62 breast, 63 and hepatocellular 64 carcinomas. TWIST1 promotes invasiveness of ALK1 ALCL cells, its expression is NPM-ALK-and STAT3-dependent, and its knockdown sensitizes the cells to ALK inhibition.…”
mentioning
confidence: 99%